Evidence-Based Practices Provided in Teacher Education and In-Service Training Programs for Special Education Teachers of Students With Autism Spectrum Disorders. (August 2019) - Hsiao, Yun-Ju; Sorensen Petersen, Sara
The purpose of this study was to investigate to what extent the identified 25 evidence-based practices were provided in teacher education and in-service training programs for special education teachers of students with autism spectrum disorder. A total of 63 participants completed the online questionnaire. The number and percentage of responses in the type of training on each evidence-based practice and all 25 evidence-based practices (total) were reported. Overall, about 60% of the participants reported that the identified evidence-based practices were either taught through direct instruction or discussed in their teacher education programs and in-service professional development. Twenty percent of the identified evidence-based practices that were addressed (i.e., "mentioned and discussed" or "mentioned and taught through direct instruction") or not addressed (i.e., "never mentioned and never taught" or "mentioned incidentally") for participating teachers were the same in these two training programs. In total, these two training programs addressed only 40% of the identified practices.